Study the Effects of Machining Parameters on Surface Roughness for Free Form Surface Using Taguchi Method - Ghazi, Safaa K.; Abdulrazaq, Mustafa M.; Sultan, Abdulrahman S.; Muhi, Firyal S. (Al-Khwarizmi Engineering Journal, 2019)
The surface finish of the machining part is the mostly important characteristics of products quality and its indispensable customers’ requirement. Taguchi robust parameters designs for optimizing for surface finish in turning of 7025 AL-Alloy using carbide cutting tool has been utilized in this paper. Three machining variables namely; the machining speeds (1600, 1900, and 2200) rpm, depth of cut (0.25, 0.50, 0.75) mm and the feed rates (0.12, 0.18, 0.24) mm/min utilized in the experiments. The other variables were considered as constants. The mean surface finish was utilized as a measuring of surface quality. The results clarified that increasing the speeds reduce the surface roughness, while it rises with increasing the depths and feeds. Using the analysis of variance, it found that the most effective variable is cutting speed with (53.85%) and the depths has the smallest influence with (20.09%). The data set from the experiments was appointed for implementing the optimum procedure, depending on the principle of Taguchi way. The result of calculation with the experimental outcome was in good agreement.